Analysis of machine-related occupational accidents in the Malaysia manufacturing industry - Rozani, Nurul Natasha; Amir, Adibah (National Institute of Occupational Safety and Health (NIOSH) Ministry of Human Resources Malaysia, 2022)
Machine-related occupational accidents can put workers at risk of amputation, illness, disability, and even death. Therefore, in this paper, data related to machinery accidents in the manufacturing sector will be analyzed because this is the biggest sector in Malaysia's gross domestic product (GDP). To gather the data, annual reports filed by the Social Security Organization (SOCSO) from 2012 to 2018 and the Department of Occupational Safety and Health (DOSH) from 2015 to 2019 were used as the primary source of occupational accident records. Analysis of SOCSO reports showed that 80.1% of the accidents occurred in men. Among all sectors, the manufacturing sector recorded the highest percentages of accidents: 28.0% and 30.7% according to the SOCSO and DOSH, respectively. Furthermore, the SOCSO recorded the highest percentage of accidents, 34.1% of which were caused by metalworking machines. Surprisingly, the total percentages of women and men who experienced accidents in the manufacturing sector for all industries were 26.1% and 23.9%, respectively. Our findings are useful for policymakers to review policies and legislations of occupational safety and health to ensure employers provide a safe workplace for their workers because the magnitude of economic costs of work-related accidents and diseases are enormous, as indicated in the percentage of GDP. Future studies should address the factors that contribute to women in the manufacturing sector having a higher percentage ratio of accidents than men.